Use Of Chitosan-Natural Zeolite Composite As Membrane Separator In Surimi Wastewater Microbial Fuel Cell - Ibrahim, Bustami; Uju, Uju; Yanti, Mudji Ana (Universitas Teuku Umar, 2023)
Microbial Fuel Cell (MFC) is a technology that uses exoelectrogenic bacteria to produce electrical energy. This study aims to determine the effect of the ratio of natural chitosan and zeolite on the characteristics of the chitosan / zeolite composite membrane as a PEM separator in MFC, to determine the performance of MFC in producing electricity, and to determine the performance of reducing the organic load of fishery wastewater in MFC technology applications. The chitosan/zeolite separator membrane was made with different ratio of chitosan and natural zeolite 1: 3, 1:1, 3: 1, and without a membrane (w/w). The chitosan / zeolite separator membrane is a proton exchange membrane that can transfer 20% positive ions. Separator membrane with a ratio of 3: 1 resulted in a tensile strength value of 0,855 MPa and a water uptake value of 1,8%, and ratio of 1:1 produced the highest conductivity value of 10,57 S/cm, the highest electric voltage was 0,59 V, the highest electric current was 0,51 mA, and the highest electric power was 0,30 mW. The values of COD, BOD, and TAN decreased by 45%, 46%, and 92%, and the pH value increased to 8,4.